Anti-Inflammatory, Antioxidant Activities, and Phytochemical Characterization of Edible Plants Exerting Synergistic Effects in Human Gastric Epithelial Cells - Achille Parfait Nwakiban Atchan; Orissa Charlène Monthe; Armelle Deutou Tchamgoue; Yeshvanthi Singh; Shilpa Talkad Shivashankara; Moorthy Karthika Selvi; Gabriel Agbor Agbor; Paolo Magni; Stefano Piazza; Uma Venkateswaran Manjappara; Jules-Roger Kuiate; Mario Dell'Agli (MDPI AG, 2023)
Dietary bioactive compounds from natural sources (e.g., herbal medicines, foods) are known to potentially suppress acute or chronic inflammation and promote the effectiveness of treatment to reduce the harmful effects of gastritis alone or in combination. In this regard, we have characterized four Cameroonian spice extracts, namely Aframomum citratum, Dichrostachys glomerata, Tetrapleura tetraptera, and Xylopia parviflora through reverse phase-high-performance liquid chromatography (RP-HPLC), ultra-performance liquid chromatography-electrospray ionization high-resolution mass spectrometry (UPLC-ESI-HRMS/MS), and Fourier transform infrared spectroscopic (FTIR) analyses and investigated their antioxidant and synergistic anti-inflammatory activities in human gastric adenocarcinoma (AGS) and gastric epithelial (GES-1) cells. The extracts showed a high amount of total phenolic (TPC: 150-290 mg gallic acid equivalents (GAE)/g of extract) and flavonoid content (TFC: 35-115 mg catechin equivalents (CE)/g of extract) with antioxidant properties in a cell-free system (1,1-Diphenyl-2-picryl-hydrazyl (DPPH) half maximal inhibitory concentration (IC50s) ≤ 45 µg/mL; 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) half maximal inhibitory concentration (IC50s) ≤ 29 µg/mL. The extracts in combination (MIX) exert a synergistic beneficial effect (combination index (CIs) < 1 and dose reduction index (DRIs) > 1) on inflammatory markers (interleukin (IL)-8 and -6 release, and nuclear factor kappa B (NF-κB) driven transcription) in human gastric epithelial cells, which may result from the presence of phenolic compounds (phenolic acids, flavonoids) or other compounds (protein, lipid, aromatic, and polysaccharide compounds) tentatively identified in the extracts. The general findings of the present study provide supporting evidence on the chemical composition of four Cameroonian dietary plants and their significant synergistic inhibitory activities on inflammatory markers of gastric epithelial cells.